Testing Application (End-to-End) Performance of Networks With EFT Traffic - Vlatko Lipovac; Vedran Batoš; Antun Sertić (Promet (Zagreb), 2009)
This paper studies how end-to-end application peiformance(of Electronic Financial Transaction traffic, in particular)depends on the actual protocol stacks, operating systemsand network transmission rates. With this respect, the respectivesimulation tests of peiformance of TCP and UDP protocolsrunning on various operating systems, ranging from Windows,Sun Solmis, to Linux have been implemented, and thedifferences in peiformance addressed focusing on throughputand response time.